Solving the climate crisis through social change public investment in social prosperity to cool a fevered planet - Lipow, Gar W. (New trends and ideas in American politics, 2012)
"This book presents an accessible and easy-to-follow argument that the climate crisis is a side effect of inequality and injustice, and demonstrates how strategies such as large-scale social investment will prove far more effective in reducing greenhouse gas pollution than cap-and-trade or other forms of free-market environmentalism"--Provided by publisher.